Bokashi as an Amendment and Source of Nitrogen in Sustainable Agricultural Systems: A Review. - Quiroz-Espinoza, M (Springer, 2019)
Integral soil fertility is managed by practices that contribute to organic matter, which improves its properties. Bokashi is an organic amendment that can be part of the tools used in sustainable soil management. This review systematizes existing information regarding the production and use of bokashi. In addition to discussing guidelines for the production and use of good-quality bokashi, it also focuses on the availability of N and microbial aspects, using compost as a reference amendment. Through this review, it was also found that (1) in order to obtain bokashi with a high N content, raw materials with a high N content must be used and, the dose of the initial C source of easy microbial assimilation should be increased. (2) Regarding the acceleration of the mineralization of the organic matter produced by the microbial inoculum, contradictory results have been obtained. Therefore, a better understanding of the interactions between the microorganisms that constitute the inoculum and the principle native microbial groups is required. (3) Few studies have evaluated the relationships between the N availability of bokashi, yield, and crop characteristics, as well as how bokashi could contribute to the fertility and availability of N when included in combination with other cultural practices. © 2019, Sociedad Chilena de la Ciencia del Suelo.